Efeitos da heterogeneidade da dívida sobre a eficiência do investimento - Sousa, Liduina Bezerra de (2025)
Decisions regarding financing and investment are essential for the financial performance of companies. These decisions can be analyzed in a specific way in order to improve extant analyses over financing and investment choices of firms. A relevant aspect of financing decisions refers to the option of firms to have a debt structure with lower or greater diversity of different types of debt, altering the degree of heterogeneity of the debt structure. With regard to investment decisions, understanding the determinants of efficient investment decisions is fundamental, since inefficient decision-making has an impact on the firm value. Given the scarcity of studies linking these two specific approaches, this research investigates the effects of debt heterogeneity on investment efficiency. The methodology used is econometric analysis with multiple linear regression with panel data. The sample includes non-financial companies listed on NASDAQ and NYSE, the two largest stock exchanges in terms of trading volume. The selected period covers the years between 2017 and 2022. The results indicate that a diversified debt structure is associated with greater investment efficiency. Additional tests reveal that the positive relationship between debt structure diversity and investment efficiency remains for companies with low bankruptcy costs and also in the period following the COVID-19 pandemic. The results indicate that borrowing different types of debt contributes to greater efficiency on investment decisions of companies due to a balance provided by the costs and benefits of these loans. There is evidence that one of the advantages brought about by a greater degree of debt heterogeneity for investment efficiency is the reduction in monitoring costs incurred by creditors. The conclusion of this study is that debt diversification is beneficial for investment decisions of firms, being a significant choice to deter firms from overinvestment or underinvestment.